Rahmah El Yunusiyah's Concept of Women's Education and the Formation of an Islamic Model of Emancipation in Minangkabau Society - Fahri Hidayat (CV. Edujavare Publishing, 2024)
Women's education constitutes one of the important issues in the history of Islamic education in Indonesia. Amid the limited access to education for women, Rahmah El Yunusiyah developed an Islamic educational model through Diniyyah Puteri that aimed to cultivate knowledgeable, morally upright, and empowered women. This study aims to analyze the philosophical foundations of women's education in the thought of Rahmah El Yunusiyah, reconstruct the concept of the Islamic Model of Women's Emancipation that she developed, and explain its contribution to the social transformation of Minangkabau women. The study employs the history of ideas method, consisting of the stages of heuristics, source criticism, interpretation, and historiography. The data sources consist of historical documents of Diniyyah Puteri, archival records, and various relevant literature. The findings reveal that women's education according to Rahmah is founded upon tawhid, the integration of knowledge, adab, self-reliance, and social responsibility. Through Diniyyah Puteri, women were prepared to become agents of change capable of integrating Islamic identity, Minangkabau tradition, and the demands of modernity. This concept represents a model of Islamic emancipation that differs from both patriarchal paradigms and secular feminism. The study concludes that Rahmah El Yunusiyah's thought offers a paradigm of Islamic education that positions education as an instrument of empowerment, character formation, and the social transformation of women within Muslim society.